Analysis Of Generation Z’s Discontinuance From Facebook: A Theory Of Planned Behavior Perspective - Febri Nurrahmi; Tanzir Masykar (Master of Communication Science Program, Universitas Diponegoro, 2026)
Facebook has experienced a shift in usage among Generation Z. Using the Theory of Planned Behavior, this study aims to explain how attitudes, subjective norms, and perceived behavioral control influence Generation Z's discontinuance of Facebook use. Data were collected through structured interviews with 15 undergraduate students at Universitas Syiah Kuala who had previously used Facebook actively. The findings reveal that attitudes toward Facebook and subjective norms are the primary factors driving informants to leave the platform. Negative attitudes emerge from concerns over the widespread circulation of hoaxes and the perception that Facebook is dominated by older users with lower levels of media literacy. Subjective norms further reinforce this discontinuance, as peer migration to alternative social media platforms shapes individual decisions. While perceived behavioral control plays a less dominant role, it still contributes to discontinuance, particularly among users who feel limited in navigating Facebook’s features and verifying information accuracy. These results highlight important implications for understanding the evolving dynamics of social media use and suggest that changing social environments and peer influence significantly shape platform abandonment among younger audiences. In conclusion, the study demonstrates that discontinuance of Facebook use is primarily socially and attitudinally driven rather than technologically constrained.